Microscopy-based methods for characterizing autophagy and understanding its dynamics in resin secretion - de Carvalho, Shelly F. [UNESP]; Scudeler, Elton L. [UNESP]; Machado, Silvia R. [UNESP] (My University, 2025)
Resin-secretory canals are a common feature of Anacardiaceae plants, and their resins have widespread applications in both industry and medicine. Cytological evidence strongly supports the occurrence of autophagy during the development of resin-secreting glands in several species of this family, including Anacardium humile. However, systematic investigations focusing on this process in these glands remain limited. This study aimed to enhance our understanding of autophagy in A. humile resin glands by elucidating its occurrence, timing, and specific mechanisms during the secretory cycle. Standard transmission electron microscopy techniques were used in conjunction with the cytochemical assays. Immunogold labeling and confocal immunofluorescence studies were conducted to identify autophagosomes and other autophagy-related structures. Two distinct types of autophagy have been identified, each associated with a specific phase of the secretory cycle. Macroautophagy predominates at the peak of secretion, whereas microautophagy occurs during the final stages of the cycle. As an integral component of the secretory process, autophagosomes degrade cytoplasmic components and organelles before fusing with the lysosomal vacuoles. In contrast to previous studies reporting extensive cellular degradation at the end of the resin-secretory cycle, often interpreted as a form of programmed cell death, no evidence of mega-autophagy was observed in this study. These findings suggest that the precise regulation of autophagy timing and intensity is crucial for maintaining the functional integrity of resin-secreting cells. Furthermore, the potential interplay between autophagic activity and terpene biosynthesis requires further investigation in the context of resin-secretory canal physiology.
Keywords: AcPase; ATG8; Immunogold labeling; Macroautophagy; Microautophagy; Ultrastruture; ZIO method